About relationship between table algebra of infinite tables and multiset table algebra - Glushko, I.M. (Інститут програмних систем НАН України, 2018)
This article is a continuation of the works devoted to the actual problem of the development of the theoretical basis of the table databases. The question of the relationship between table algebra of infinite tables and multiset table algebra is considered. Considering the fact that 1-multisets are analogues of ordinary sets, the question arises, is whether table algebra of infinite tables a subalgebra of multiset table algebra. This paper is devoted to this issue. Applying the theorem-plural and logical-algebraic methods found that this is not the case. The table algebra of infinite tables does not form subalgebra of multiset table algebra, since it is not closed in relation to some signature operations of multiset table algebra. These operations are determined.Problems in programming 2018; 2-3: 158-163